Structuring construction of space. Materiality in Lucio Muñoz and Amalia Avia´s house. Architect Fernando Higueras - Arcaraz Puntonet, Jon (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
Lucio Muñoz and Amalia Avia´s house, built in Arroyo de Trofas, in Torrelodones, by Fernando Higueras was characterized by its organic quality: it organically adapted to the plot conditions. However, at the same time, it could be qualified as an organicist intervention, since it grew in space and time like an organism. Through stacking constructive elements, it developed a structuring construction of space. Once the structure was defined, the growth of its form through the sequence of dwelling elements enabled it to adapt to the external factors of the environment. Both ways of organising matter, the stacking and the sequence, were characterized by the stratification of the whole series of elements. This strategy was what created, on the one hand, the dematerialisation of the ensemble in space, which contrasted with the materiality with which the house was built. On the other hand, it established the opposition between the gravity and the lightness with which the growth of its form was perceived.
Keywords: Organic; Organicist; Stacking; Stratification; Dematerialisation; Adaption